Pediatric Ventriculoperitoneal Shunts Revision Rate and Costs in High-Volume sub-Saharan Department - Vlasák, Aleš; Okechi, Humphrey; Horinek, Daniel; Albright, A Leland (World neurosurgery, 2019)
BACKGROUND: Ventriculoperitoneal shunt (VPS) placement is one of the most common neurosurgical procedures. VPSs are associated with high costs, which predominantly arise from relatively high complication and revision rates. It is reasonable to assume that revision rates in developing countries would be higher. In this study we report the single-institution revision rates and costs from a high-volume department in sub-Saharan Africa. METHODS: A pediatric neurosurgical database was studied in the extent of 5 years. The 30-day shunt failure rate, overall revision rate, and costs were calculated, and results were compared with previously published studies from developed countries. RESULTS: In the selected time period 1840 VPS surgeries were performed, of which 592 were shunt revisions (32.14%). The majority of revision surgeries was performed in the first year- 501 (representing 84.63%); second year, 64; third year, 21; fourth year, 6; and fifth year, 2. The overall shunt revision rate was 28.94% with a 30-day revision rate of 14.58%. During the course of the study, costs of VPS surgery, the shunt, and daily ward charges did not change significantly. The average total charge for VPS insertion was 60,000 KES (586 USD), VPS removal 30,000 KES (293 USD), and VPS revision 50,000 KES (489 USD). CONCLUSIONS: This retrospective study proves that VPSs, with their known complication risks, can be performed in a sub-Saharan missionary hospital with acceptable costs and results that are comparable with those achieved in some Western hospitals. Keys to those outcomes include high volume and a highly experienced team.
Keywords: Female; dítě; pediatrie; ventrikuloperitoneální zkrat; ženské pohlaví; lidé; Neurosurgical Procedures; následné studie; délka pobytu; nemocnice - náklady; Hospital Costs; neurochirurgické výkony; Length of Stay; Reoperation; Africa South of the Sahara; reoperace; retrospektivní studie; Follow-Up Studies; Male; Ventriculoperitoneal Shunt; subsaharská Afrika; Child; Pediatrics; mužské pohlaví; Retrospective Studies; Humans